Mutational Analysis of Ocriplasmin to Reduce Proteolytic and Autolytic Activity in Pichia pastoris - Baghban, Roghayyeh (Biol Proced Online, 2020)
BACKGROUND: Ocriplasmin (Jetrea) is using for the treatment of symptomatic vitreomacular adhesion. This enzyme undergoes rapid inactivation and limited activity duration as a result of its autolytic nature after injection within the eye. Moreover, the proteolytic activity can cause photoreceptor damage, which may result in visual impairment in more serious cases. RESULTS: The present research aimed to reduce the disadvantages of ocriplasmin using site-directed mutagenesis. To reduce the autolytic activity of ocriplasmin in the first variant, lysine 156 changed to glutamic acid and, in the second variant for the proteolytic activity reduction, alanine 59 mutated to threonine. The third variant contained both mutations. Expression of wild type and three mutant variants of ocriplasmin constructs were done in the Pichia pastoris expression system. The mutant variants were analyzed in silico and in vitro and compared to the wild type. The kinetic parameters of ocriplasmin variants showed both variants with K156E substitution were more resistant to autolytic degradation than wild-type. These variants also exhibited reduced K(cat) and V(max) values. An increase in their Km values, leading to a decreased catalytic efficiency (the K(cat)/K(m) ratio) of autolytic and mixed variants. Moreover, in the variant with A59T mutation, K(cat) and V(max) values have reduced compared to wild type. The mix variants showed the most increase in Km value (almost 2-fold) as well as reduced enzymatic affinity to the substrate. Thus, the results indicated that combined mutations at the ocriplasmin sequence were more effective compared with single mutations. CONCLUSIONS: The results indicated such variants represent valuable tools for the investigation of therapeutic strategies aiming at the non-surgical resolution of vitreomacular adhesion.